2013
DOI: 10.1371/journal.pone.0058393
|View full text |Cite
|
Sign up to set email alerts
|

Codon Optimization Significantly Improves the Expression Level of a Keratinase Gene in Pichia pastoris

Abstract: The main keratinase (kerA) gene from the Bacillus licheniformis S90 was optimized by two codon optimization strategies and expressed in Pichia pastoris in order to improve the enzyme production compared to the preparations with the native kerA gene. The results showed that the corresponding mutations (synonymous codons) according to the codon bias in Pichia pastoris were successfully introduced into keratinase gene. The highest keratinase activity produced by P. pastoris pPICZαA-kerAwt, pPICZαA-kerAopti1 and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 36 publications
4
36
0
1
Order By: Relevance
“…Taken together, these observations strongly suggested that KERQ7 was a monomeric protein comparable to those previously reported for other keratinases from Bacillus strains [15,25,27,[29][30][31].…”
Section: Purification and Molecular Weight Determination Of Kerq7 Enzymesupporting
confidence: 88%
See 1 more Smart Citation
“…Taken together, these observations strongly suggested that KERQ7 was a monomeric protein comparable to those previously reported for other keratinases from Bacillus strains [15,25,27,[29][30][31].…”
Section: Purification and Molecular Weight Determination Of Kerq7 Enzymesupporting
confidence: 88%
“…Lane 3, dialyzed sample obtained after ammonium sulfate fractionation 30-60% (30 g). Lane 4, purified keratinase KERQ7 (30 g) obtained after S Sepharose cation-exchange chromatography (fractions[28][29][30][31][32][33][34][35], and (C) Zymogram activity staining of the purified keratinase using keratin azure as a substrate.Pyrase ® 250 MP, and KERQ7 retained 70, 73, 80, and 90% of their activity at pH 5 after 240 h incubation at 30 • C, respectively. At pH 7, and using keratin azure as substrate, KERQ7, Koropon ® SC 5K, Basozym ® CS 10, and Pyrase ® 250 MP, were optimally active at 25, 30, 30, and 35 • C in the absence of CaCl 2 and at 30, 35, 35, and 40 • C, respectively in the presence of 1 mM Ca 2+…”
mentioning
confidence: 99%
“…Gene sequence optimization has been a widely effective measure to increase heterologous protein expression levels in P. pastoris (32)(33)(34)(35)(36), but the mechanism behind this strategy has seldom been studied. The results presented herein are consistent with prior insights that premature transcription termination may result from short segments of severe nucleotide bias within some native genes (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…The yeast was transformed with 1 μg of Sac I-linearized pPICZα A-RMlip by the spheroplast method of Cregg et al (1985) Cultivation. Standard cultivation method was carried out according to method described in Hu et al (2013) and Wang et al (2016). A single positive colony o was cultivated in 100 mL of BMGY medium at 30 C overnite under constant agitation at 250 rpm, until an OD = 2-5 was reached.…”
Section: Methodsmentioning
confidence: 99%